Biohybrid cellulose fibers: Toward paper materials with wet strength properties. (1st August 2018) - Mangiante, Gino; Alcouffe, Pierre; Gaborieau, Marianne; Zeno, Elisa; Petit-Conil, Michel; Bernard, Julien; Charlot, Aurélia; Fleury, Etienne
Graphical abstract: Highlights: PEG grafting on cellulose fibers with DS up to 0.028. Biohybrid papers present good mechanical properties in the wet state. Immersed in water, crosslinked biohybrid papers present higher stability. Abstract: Herein, we report on the preparation of novel cellulose-PEG biohybrid papers with wet strength properties. The biohybrid paper sheets are obtained using a two-step procedure where ω- or α, ω-azide functionalized PEG chains are anchored onto alkyne-functionalized wood fibers through CuAAC ligation in mild and aqueous conditions. The incorporation of the PEG grafts mostly occurs at the periphery of the cellulose fibers and degrees of substitution up to 0.028 are obtained. The presence of PEG grafts significantly increases the tensile, burst and tear strength properties in the wet state, the reinforcement being more pronounced for fibers grafted with α, ω-azide PEG. This reinforcement is consistent with a relatively sparse hetero-crosslink reaction creating inter-fiber covalent bonds and forming a cellulose network within the cell wall.